Safety planning with battered women complex lives/difficult choices - Davies, Jill (Jill M.); Lyon, Eleanor; Monti-Catania, Diane; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1998)
This book draws attention to the complexity of helping battered women and their children. The authors introduce a new model of women-defined advocacy that emphasizes several topics, including understanding a battered woman's perspective.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Abused women -- Counseling of; Social work with women; Wife abuse -- Prevention; Social advocacy; Electronic books